A Qualitative Study Exploring the Perceptions and Experiences of Parents and Carers of People with Learning Disabilities When Accessing Healthcare - Sullivan, Charlotte (2011)
Historically people with learning disabilities (LD) have been subjected to discrimination, segregation, poor standards of care and even violence and abuse. Government policies have evolved with a changing society to incorporate people with LD into mainstream care with the most recent policies Valuing People (DoH, 2001) and Valuing People Now (DoH, 2009). Healthcare is of huge concern to people with LD and this has been accounted for in these policies. The healthcare of people with LD still, however, faces challenges. There is also a lack of assessment of the current policies and procedures, taking into account the views of those involved in the care of people with LD. This is a qualitative study exploring the views of parents and carers of people with LDs when accessing healthcare. A sample of seven participants, all carers or parents of people with LD, were interviewed. The transcripts of these interviews were analysed using the generic qualitative approach and three themes were identified: bad memories from the past, how things are now and hopes for the future. The results showed show consistencies with the literature reviewed regarding this subject, however, inconsistencies were also noted. The need for better nursing education regarding LD, for all branches, was identified and recommendations have been made for future nursing education, practice and research. The limitations of this study have been acknowledged and, even in light of these, it is hoped that this study contributes positively to research into healthcare for people with LD.